Hospital postdischarge intervention trialled with family caregivers of older people in Western Australia: potential translation into practice. Issue 11 (8th November 2018) - Aoun, Samar M; Stegmann, Roswitha; Slatyer, Susan; Hill, Keith D; Parsons, Richard; Moorin, Rachael; Bronson, Mary; Walsh, Debbie; Toye, Christine
Abstract : There is lack of a suitable assessment tool that can be used routinely and systematically by hospital staff to address family caregivers' (FCs') support needs. This paper describes a novel approach to identifying and addressing FCs' needs following hospital discharge of the older person receiving care. Setting and participants: FC recruitment occurred on the patient's discharge from a tertiary hospital in Western Australia; 64 completed the study; 80% were female; mean age 63.2 years. Intervention: The Further Enabling Care at Home (FECH) programme was delivered over the telephone by a specially trained nurse and included: support to facilitate understanding of the patient's discharge letter; caregiver support needs assessment and prioritisation of urgent needs; and collaborative guidance, from the nurse, regarding accessing supports. Results: Sixty-four FCs completed the FECH programme. The top three support needs identified by the FCs were: knowing what to expect in the future (52%), knowing who to contact if they were concerned (52%) and practical help in the home (36%). The telephone-based outreach service worked well and was convenient for the nurse and the FCs, and saved on transport, time and money. Most of the FCs appreciated the systematic approach to identify and articulate their needs and were satisfied with the support they received, mainly navigation through the systems, problem solving, self-care strategies, explanation of illness, symptoms and medication and access to after-hours services. Conclusions: In order to guide services which may consider adopting this systematic approach to supporting FCs and integrating it into their routine practice, this evaluation of the FECH programme has described the processes implemented and highlighted the factors that hindered or facilitated these processes to engage caregivers with appropriate services in a timely manner. Positive feedback indicated that the programme was a useful addition to hospital discharge planning. Trial registration number: ACTRN12614001174673; Results.